Research results on the Zooplankton in TamGiang - Cau Hai lagoon system, Thua Thien - Hue provice - Tuan, Le Cong; Linh, Nguyen Quang; Mong, Nguyen (Academia Journal of Biology, 2015)
Data were received from quantitative and qualitative analyses of 1584 samples collected in Tamgiang - Cauhai lagoon system. 42 species belonging to 20 families, 3 orders, 2 classes, 2 phylylums of zooplankton were identified from this lagoon system. The results also shown that, there were 4 distribution zones of zooplankton with different genus and species composition. The dynamic features in species composition as well as in quantity of zooplankton in this lagoon system during the research period 1998-2000 were recorded.